Y and W Chromosome Assemblies: Approaches and Discoveries - Tomaszkiewicz, Marta; Medvedev, Paul; Makova, Kateryna D. (Trends in genetics, 2017)
Hundreds of vertebrate genomes have been sequenced and assembled to date. However, most sequencing projects have ignored the sex chromosomes unique to the heterogametic sex – Y and W – that are known as sex-limited chromosomes (SLCs). Indeed, haploid and repetitive Y chromosomes in species with male heterogamety (XY), and W chromosomes in species with female heterogamety (ZW), are difficult to sequence and assemble. Nevertheless, obtaining their sequences is important for understanding the intricacies of vertebrate genome function and evolution. Recent progress has been made towards the adaptation of next-generation sequencing (NGS) techniques to deciphering SLC sequences. We review here currently available methodology and results with regard to SLC sequencing and assembly. We focus on vertebrates, but bring in some examples from other taxa. NGS technology and advances in assembly algorithms allow researchers to decipher chromosomes Y and W, the most challenging parts of vertebrate genomes to sequence and assemble. The rapidly accumulating data accelerate discoveries related to the evolution and structure of these chromosomes, suggesting that they are much more varied among vertebrate species than was previously realized. Y and W chromosome data are being used to trace the divergence of male- and female-specific lineages. Novel technology makes it possible to generate population-scale sequencing data for these chromosomes and to study their diversity.